1990
DOI: 10.1007/bf00571428
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of 14 kDa ?-galactoside-binding lectin in various organs of rat

Abstract: Immunohistochemical localization of 14 kDa beta-galactoside-binding lectin in various organs of adult rat was achieved using a monospecific antibody raised against lectin purified from rat lung. The antibody-stained cells were formed into small aggregates, thin fascicles, or thick bundles in the walls of blood vessels, gastrointestinal tracts and urogenital organs. From the patterns of distribution, as well as their organization, these immunoreactive cells were regarded as smooth muscle cells. This was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
19
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
6
19
0
Order By: Relevance
“…Some of the cells in the myometrium had strong intracellular staining, whilst other smooth muscle cells showed staining only at the periphery. Similar findings have been reported with both rat and rabbit tissues (Cart et al, 1987;Wasano et al, 1990) although the reason why the lectin is located both intracellularly and extracellularly is not clear. Vascular smooth muscle showed variable staining.…”
Section: Discussionsupporting
confidence: 77%
“…Some of the cells in the myometrium had strong intracellular staining, whilst other smooth muscle cells showed staining only at the periphery. Similar findings have been reported with both rat and rabbit tissues (Cart et al, 1987;Wasano et al, 1990) although the reason why the lectin is located both intracellularly and extracellularly is not clear. Vascular smooth muscle showed variable staining.…”
Section: Discussionsupporting
confidence: 77%
“…Our data are in concordance with those obtained in mice (Poirier et al, 1992), that showed galectin-1 expression by in situ hybridization in the myotomes of the somites and in some neural cells. Expression of galectin-1 in adult muscle cells has been already documented (Southan et al, 1987;Cooper and Barondes, 1990;Wasano et al, 1990;Cooper et al, 1991;Tracey et al, 1992). Our data demonstrate that expression of galectin-1 in muscle cells can be detected already in first trimester, in full agreement with data implicating galectin-1 in muscle differentiation (Cooper et al, 1991).…”
Section: Discussionmentioning
confidence: 87%
“…In rabbit and rat, abundant expression has been attributed to smooth muscle cells, as supported by the application of a monoclonal antibody against smooth muscle Îą-actin (Catt and Harrison 1985;Wasano et al 1990). Our study concludes that this expression pattern does not hinge on the individual organization of the tissue.…”
Section: Discussionmentioning
confidence: 98%